2013
DOI: 10.1136/bmjopen-2012-001847
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of health effects of large industrial incinerators in England, 1998–2008: a study using matched case–control areas

Abstract: ObjectivesTo assess whether residential proximity to industrial incinerators in England is associated with increased risk of cancer incidence and mortality.DesignRetrospective study using matched case–control areas.SettingFive circular regions of radius 10 km near industrial incinerators in England (case regions) and five matched control regions, 1998–2008.ParticipantsAll cases of diseases of interest within the circular areas.Primary and secondary outcome measuresCounts of childhood cancer incidence (<15 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…With regard to childhood leukemias and the pollution sources analyzed in our previous papers, our findings about proximity to industrial groups (see Table 4) are consistent with other studies in relation to the excess risk found in the environs of the metal industry (which includes ‘Production and processing of metals’, ‘Galvanization’, and ‘Surface treatment of metals and plastic’) [28, 29] and installations for the manufacture of ‘Glass and mineral fibers’ [28], although other authors did not find associations with proximity to incinerators (‘Hazardous waste’) [15]. In relation to specific carcinogens and groups of pollutants, some authors found a possible increased risk of some types of childhood leukemias in children living within 3 km of industrial dichloromethane releases (OR 1.64; 95% CI 1.15–2.32) [30], very similar to our results for this pollutant at 2.5 km (OR 1.65; 95% CI 1.11–2.45).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to childhood leukemias and the pollution sources analyzed in our previous papers, our findings about proximity to industrial groups (see Table 4) are consistent with other studies in relation to the excess risk found in the environs of the metal industry (which includes ‘Production and processing of metals’, ‘Galvanization’, and ‘Surface treatment of metals and plastic’) [28, 29] and installations for the manufacture of ‘Glass and mineral fibers’ [28], although other authors did not find associations with proximity to incinerators (‘Hazardous waste’) [15]. In relation to specific carcinogens and groups of pollutants, some authors found a possible increased risk of some types of childhood leukemias in children living within 3 km of industrial dichloromethane releases (OR 1.64; 95% CI 1.15–2.32) [30], very similar to our results for this pollutant at 2.5 km (OR 1.65; 95% CI 1.11–2.45).…”
Section: Discussionsupporting
confidence: 88%
“…Positive results or positive associations found in both approaches support and reinforce the hypothesis of a “real” excess risk in the vicinity of the pollution sources analyzed in the study. However, the main limitation of these methodological approaches is the choice of the radius in the “ near vs. far ” analysis and the critical categorization in concentric rings in the “ risk gradient ” analysis, although our industrial distances are in line with the distances used by other authors [1315]. Another limitation is the assumption of the linear trend in the risk in the “ risk gradient ” analysis, something that might not be true.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas the results of a Taiwanese study showed that children who lived in municipalities with highest levels of petrochemical air pollution had a statistically significant higher risk of developing leukemia (Weng et al, 2008), and a review found increased risk of childhood leukemia with residential addresses near gas stations and nuclear power plants (Brender et al, 2011), other studies did not find evidence of risk of childhood leukemia in the vicinity of incinerators (Reeve et al, 2013) or petrochemicals (Yu et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The dimension of these blocks may vary greatly depending on the location: normally these blocks are smaller in populated areas but may become very large in other rural zones. Moreover, no information was generally given about blocks extension, and it was difficult to compare very different blocks types like Small Area Health Statistic Unit (SAHSU) [35], UK census postcode system [59], or UK Lower Layer Super Output Areas (LSOA) [60]. In our case study census blocks had an average area of 0.4 km 2 (min: 968.4 m 2 ; max: 6.3 km 2 ) and contained on average 26 addresses (min: 1; max: 130): both address distances and concentrations vary widely inside some census blocks (Figures 4(c) and 4(d)).…”
Section: Discussionmentioning
confidence: 99%